Analisis Pengaruh Kebiasaan Belajar, Minat Belajar, Lingkungan Belajar Siswa Terhadap Prestasi Belajar Pemrograman Dasar Kelas X Teknik Komputer dan Jaringan (Studi Kasus: SMKN 5 Malang) - Ramadhana Setiyawan; Retno Indah Rokhmawati; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
This study is a descriptive study designed to discuss the implications of learning habits, learning interests, and learning environments on the learning progress of Basic Class X programming in computer and network technology in SMK 5 Malang. Data collection uses a questionnaire methodology to obtain data related to study habits, learning interests, learning environment, and the use of documentation methods to determine students' learning performance. This study also uses a purposive methodology with a population of 80 students in Class X computer and network engineering from SMKN 5 Malang. The instrument tests were conducted by 32 students in Class XI computer and network technology. Multiple linear regression was used to analyse the data before being entered into the analysis step, the data was first tested using the analysis precondition test, and the results of the data were normalized, linear, and there was no heterokesdastisitas.This study found that (1) partially learning habits have a positive and significant impact on class X computer and network learning performance at Malang 5 Vocational High School, (2) partially learning interests have a negative and significant impact on basic programming skills, (3)Learning Achievements Have Class X Computer and Networking Technology at Malang Vocational Secondary School 5 Partly the learning environment is not significant, but it does have a positive impact on the learning performance of basic programming in Class X computer and network engineering at SMK 5 in Malang, (4) Simultaneity Learning interest, learning environment has an impact on the learning performance of basic programming in Class X of computer and network technology in SMK 5 Malang and is significant.